Pengaruh komposisi media tanam terhadap pertumbuhan rumput gajah mini variegata (Axonopus compressus) - Sinaga, Putra Diangga; Ruliyansyah, Agus; Pramulya, Muhammad (Jurnal Arsitektur Lansekap, 2018)
Effect of the composition of planting media on the growth of pearl grass variagated (Axonopus Compresuss). Pearl grass variagated (Axonopus compresuss), is a kind of ornamental grass used as landscape grass or carpet grass. Planting pearl grass variegated at this time, just plowing land, only ultisol. These conditions cause the growth of slow grass, easy soil erosion, then it takes quite a long time to cover the land. Because Ultisol is poor for nutrients and has a solid soil structure, it requires a mixture of organic composition to add nutrients and improve soil structure to loose. Therefore Organic materials used such as sawdust and cow dung manure. The objective of the research is knowing the composition of planting media consists of, Ultisol (PMK), sawdust (SG) and cow‘s manure (KS) on planting of pearl grass variegated. Planting is done on the map with size 0.5 m x 0.5 m. This research used Completely Randomized Design () with 6 treatments, 5 replicates, each replication consist 25 plant and sampling 20%. Treatment for compositions such as m0 (PMK 100%), m1 (PMK 75%: SG 25%), m2 (PMK 75%: PS 25%), m3 (PMK 50%: SG50%), m4 (PMK 50%: PS 50%), m5 (PMK 50%, PS 25%, SG 25%). The research was done for approximately 3 months from mid August to November 2017 in experimental garden Faculty of Agriculture UNTAN. The Research shows that the composition of planting media have significant effect on observation variables, such as number of tillers, stolon length, cover area, root length and dry weight. The result of this research shows, the treatmen of m4(PMK 50% : PS 50%) has higher value among of other treatment.